To Identify Drug-Drug Interaction in Cardiac Patients in Tertiary Care Hospitals - Sultana, Amreen; Singh, Malvika; Kumar, Ajay; Kumar, Roshan; Saha, Purabi; Kumar, Ravi Shankar; Kumar, Devinder (Journal for Research in Applied Sciences and Biotechnology, 2022)
The potential for drug-drug interactions (pDDIs) is higher with cardiac medications, and reports of pDDIs in cardiovascular patients are more common. Multimorbidity, a greater number of drugs prescribed, longer hospital stays, complexity of disease, physiological changes with advancing age or conditions like renal failure, shock, hepatic disease like cirrhosis or acute viral hepatitis, stages of disease, and the influence of heart disease on drug metabolism make patients with CVD especially susceptible to DDIs. Our research found that pDDIs occurred at a much higher rate than expected in the Cardiology Division. Incidence of pDDIs was observed to rise with age, polypharmacy, and duration of hospital stay; pDDIs were also more common in males than females. Most of the interactions were of a pharmacodynamic character and were considered to be quite serious. Most pDDIs involved aspirin and clopidogrel, then aspirin and enalapril, and finally enalapril and enalapril. The surveillance of pDDIs in cardiac inpatients may benefit from the creation of such a database in hospitals.